IMPLEMENTASI NAFKAH IDDAH DI PENGADILAN AGAMA LUBUK LINGGAU - Fuadi, Ahmad Fuadi; Anggreni, Devi; Fitriyani, Sy (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The court has the authority to demand that the former husband provide post-divorce living expenses in the form of nafkah iddah. The Religious Court plays a central role in ensuring the rights of wives after divorce. When nafkah iddah is not implemented properly, it can result in injustice for women. When such injustice occurs, it is important to conduct a thorough investigation to find effective solutions for law enforcement, especially in ensuring the fulfillment of women's rights after divorce. This study utilizes a normative-empirical approach. Data collection is conducted through literature review, documentation, observation, and interviews. The results of this study show that the payment of nafkah iddah in divorce is carried out during the implementation of the talak pledge session, namely before the pronouncement of talak. This is done to protect the rights of women post-divorce, and the protection of women is an effort to create gender justice, which is increasingly becoming a concern. One of the measures is to determine the period of payment for nafkah iddah during the implementation of the talak pledge session.